MENINGKATKAN KESADARAN MAHASISWA STKIP PGRI SUKABUMI UNTUK BERPERILAKU ANTI KORUPTIF MELALUI PENDIDIKAN ANTI KORUPSI - Asma Nurani Nugrahawati (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2023)
The article is titled Increasing the Awareness of STKIP PGRI Sukabumi Students toward Anti-Corruptive Behavior through Anti-Corruption Education. Broadly speaking, the issue discussed is the students’ awareness of their role as agents of change in addressing corruption in Indonesia and the crucial role of anti-corruption education in enhancing legal awareness. This study employs a qualitative approach using a case study method, incorporating both factual and conceptual approaches, and is presented in an analytical descriptive manner. The results of the study indicate that the younger generation has sufficient knowledge about corruption, the various forms of corruption, and anti-corruptive behavior. However, this adequate knowledge has not yet been accompanied by the willingness to act in an anti-corruptive manner. This indicates a weakness among students in terms of awareness to develop an anti-corruption culture within themselves. Therefore, it can be concluded that there is a need for anti-corruption education for the younger generation to help foster their legal awareness and promote anti-corruptive behavior.